The Students’ Needs in Developing EFL Materials ICT Based - Muthmainnah; Nur Aeni; Mohammed Galal; K. J. Varghese; Fides Del Castillo; Abd. Ghofur; Nur Aeni (IAIN MADURA, 2021)
In developing English communication skills, the student's needs, wants, and lacks are crucial. The materials given should be suitable for the students' wants. These issues are vital in developing any English materials on ICT-based. This study explores the students' needs, wants, and lacks in learning English by developing suitable materials with the ICT-based. The mixed approach was used in this study. The researchers distributed the survey to 350 students from Indonesia and other countries (Kosovo, Kuwait, Ghana, Pakistan, Philippines, India, and United Kingdom) involved in the Share to Care Community in collecting the data. They were assigned to fill the Google form about their needs in learning English. The result showed that the students need materials that fulfill their needs. It should be related to today's facts, easy enough to share with, and easy to access by the students' technologies devices, then using both target languages L2 and L1 to deliver the materials. While teaching, the lecturers used any method; role-playing is the most common, followed by oral reports, games, outdoor learning, and blended learning. Most of the students from several countries intended to have ICT in their learning process.